(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to highlight the importance of identifying and measuring costs using strategic cost management techniques, including the time-oriented resource consumption accounting technique in the pricing of hotel service instead of the traditional methods of calculating costs, as the researcher used the inductive method in the theoretical aspect by conducting a survey of studies that presented the research variables in order to extract ideas and compile the theoretical foundations presented in local, Arab and foreign books, theses, dissertations and periodicals and using the analytical method in the practical aspect in linking the research variables (the independent variable of the time-oriented resource consumption accounting technique) with the research variables (independent variable of the time-oriented resource consumption accounting technique) and using the analytical method in the practical aspect in the link between the research variables (independent variable of the hotel service pricing and the costing of the hotel service.